Prophetic dialogue: The quest for religious leaders seeking reconciliation in the aftermath of the transition in South Africa? - Christo H. Thesnaar (Verbum et Ecclesia, 2017)
The TRC re-enactment consultation18 afforded the opportunity to reflect on the leadership of religious leaders during the apartheid era, and in the years that followed. This chapter is particularly interested in the prophetic leadership provided by religious leaders during apartheid, and 20 years following the transition by engaging with some normative thoughts on prophetic dialogue. The findings on the leadership provided during the post-TRC are reflected upon in terms of reconciliation through the hermeneutical lens of the Belgian scholar Valarie Rosoux. Hereby, this chapter seeked to contribute to reconciliation and national unity in the current South African context with some strategic conclusions to ensure that the process of reconciliation becomes a priority for all faith communities across the nation.